Multiple variability of summer sea surface temperature (SST) and evaporation over the Indian Seas (MAUSAM, 1999)
Utilising thirty one years' marine meteorological data from 1961-91 recorded over the north Indian Ocean the sea surface temperature (SST) and evaporation have been obtained for different regions of the Arabian Sea and the Bay of Bengal. The moving pentad averages of SST and evaporation reveal increasing tendencies of both the parameters over the Arabian Sea and that of evaporation over the Bay of Bengal during May. The changes are real and significant as revealed by the trend analysis. The spectral analysis shows that SST has a 2-3 year significant cycle and evaporation rate has a 2-5 year cycle over the Indian Seas. In addition, a significant 15-year cycle is present in the SST over the Bay of Bengal and evaporation rate over the Arabian Sea. Empirical orthogonal function analysis performed on the anomalies of SST and evaporation rate over the Arabian Sea and the Bay of Bengal reveals that the time coefficient of first EOF has an increasing tendency.